EDITORIAL: Critical psychology - Hayes, Grahame (PINS-Psychology in Society, 2026)
It will not have escaped the attention of PINS subscribers and readers that the journal has been appearing irregularly for some time. More accurately, PINS has been appearing regularly, albeit too infrequently. There are many complex reasons behind this state of affairs, and in this special issue on Critical Psychology, it is worth commenting on some of the issues and problems that inform the production of certain intellectual projects.